A surface-engineered NIR light-responsive actuator for controllable modulation of collective cell migration. Issue 36 (27th August 2019) - Liu, Jiayu; Shang, Jinhui; Chen, Yancao; Tian, Yueyue; Yang, Qian; Chen, Mei; Xiong, Bin; Zhang, Xiao-Bing
Abstract : A surface-engineered NIR light-responsive actuator has been presented for manipulating collective cell migration by activating mechanical signal transduction in live cells. Abstract : Mechanical signal transduction is fundamental for maintaining and regulating cellular processes and functions. Here, we proposed a novel near-infrared (NIR) light-responsive optomechanical actuator for the directional regulation of collective cell adhesion and migration. This optomechanical actuator that is made up of a thermal-responsive copolymer hydrogel and gold nanorods (AuNRs), enables non-invasive activation by NIR light stimulation. The activation of the optomechanical actuator leads to hydrogel contraction and an increase in Young's modulus, which could be used for applying contraction force to cells cultured on the surface of the hydrogel actuator. By grafting cell adhesive peptide ligands, the cells could attach onto the surface of the actuator and displayed a NIR light illumination intensity dependent migration rate along a random orientation. To achieve the controllable modulation of cell behaviors, we employed a microcontact printing strategy for patterned presentation of adhesive ligands on this actuator and achieved directional cell alignment and cell migration through optomechanical actuation. These demonstrations suggest that this robust optomechanical actuator is promising for the optical modulation of cellular events and cell functions in various bioapplications.